1996
DOI: 10.1002/(sici)1096-9861(19960506)368:3<335::aid-cne2>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional and laminar differences in synaptic localization of NMDA receptor subunit NR1 splice variants in rat visual cortex and hippocampus

Abstract: Changes in N-methyl-D-aspartate (NMDA) receptor expression may represent a molecular substrate for differences in synaptic plasticity between early postnatal and adult brains (Fox and Zahs [1994] Curr. Opinion Neurobiol. 4:112-119). We have, therefore, examined the regional and laminar distribution of NR1, the essential subunit of the NMDA receptor, in two regions in which synaptic plasticity has been most thoroughly studied: primary visual cortex and hippocampus. To study NR1 expression at the light and elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 76 publications
5
31
1
Order By: Relevance
“…Slight differences in the relative level of staining in some brain regions between AGS and rats were observed. For example, we found equally dense staining in CA1, CA3, dentate gyrus, and hilus regions in AGS hippocampus while, in rats, others have found denser staining in CA1 and CA3 (Petralia et al, 1994) or in CA1 and the hilus region of the dentate gyrus (Johnson et al, 1996). These disparities may be due to strain or species differences or to a difference in antibodies used.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Slight differences in the relative level of staining in some brain regions between AGS and rats were observed. For example, we found equally dense staining in CA1, CA3, dentate gyrus, and hilus regions in AGS hippocampus while, in rats, others have found denser staining in CA1 and CA3 (Petralia et al, 1994) or in CA1 and the hilus region of the dentate gyrus (Johnson et al, 1996). These disparities may be due to strain or species differences or to a difference in antibodies used.…”
Section: Discussioncontrasting
confidence: 45%
“…Localization of NR1 reflects localization of the majority, if not all, NMDAR complexes (Forrest et al, 1994;Sakimura et al, 1995;Nakanishi, 1992). The purpose of this study was, therefore, to characterize the distribution of NR1 subunits in the central nervous system of Arctic ground squirrels (AGS, Spermophilus parryii) using a NR1 antibody, which has been well characterized in rats and other species such as mouse, monkey, and human (Johnson et al, 1996;Bilak et al, 1995;Siegel et al, 1994;Huntley et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…8). In the visual cortex, mGluR5 is present in layers where thalamic fibers terminate (Reid et al 1995), while NMDARs or the NR1 subunit are primarily concentrated in superficial layers (Johnson et al 1996;Rosier et al 1993). These reports suggest that mGluR5 is present mainly at thalamo-cortical synapses, while NMDARs are at cortico-cortical synapses.…”
Section: Roles Of Mglurs In Thalamo-cortical Synapses and Those Of Nmmentioning
confidence: 99%
“…As the neurons mature, the abundance of NR1-NR2A and NR1-NR2A-NR2B heteromers increased (1). Electrophysiological and immunocytochemical evidences showed that in mature neurons, NMDA receptors primarily clustered at excitatory synapses, which were localized on dendritic spines (2)(3)(4)(5)(6)(7)(8). To achieve this specific distribution, NMDA receptors undergo regulations in various trafficking steps, including de novo exocytosis, endocytosis, recycling, lateral movement between synaptic and extrasynaptic membranes, and stabilization by synaptic scaffolding proteins (1,9).…”
mentioning
confidence: 99%